2008
DOI: 10.1016/j.exppara.2008.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Entamoeba histolytica: Lipid rafts are involved in adhesion of trophozoites to host extracellular matrix components

Abstract: Adhesion is an important virulence function for Entamoeba histolytica, the causative agent of amoebic dysentery. Lipid rafts, cholesterol-rich domains, function in compartmentalization of cellular processes. In E. histolytica, rafts participate in parasite-host cell interactions; however, their role in parasite-host extracellular matrix (ECM) interactions has not been explored. Disruption of rafts with a cholesterol extracting agent, methyl-beta-cyclodextrin (MbetaCD), resulted in inhibition of adhesion to col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…There are intriguing correlations between E. histolytica virulence and cholesterol. For example, cholesterol has been shown to enhance virulence functions in E. histolytica, including adhesion (27,28), expression of ConA binding sites on the cell surface (63), and hemolytic and erythrophagocytic activity (64). Several studies have demonstrated that it is possible to revive the virulence of avirulent E. histolytica strains by supplying medium with cholesterol (65,66) or by repeated passage through liver, which is a major site of cholesterol synthesis (67).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There are intriguing correlations between E. histolytica virulence and cholesterol. For example, cholesterol has been shown to enhance virulence functions in E. histolytica, including adhesion (27,28), expression of ConA binding sites on the cell surface (63), and hemolytic and erythrophagocytic activity (64). Several studies have demonstrated that it is possible to revive the virulence of avirulent E. histolytica strains by supplying medium with cholesterol (65,66) or by repeated passage through liver, which is a major site of cholesterol synthesis (67).…”
Section: Discussionmentioning
confidence: 99%
“…Dialkyindocarbocyanine (DiIC 16 ; Invitrogen) staining of lipid rafts was carried out as described previously (27).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations